2012
DOI: 10.1007/978-1-61779-927-3_22
|View full text |Cite
|
Sign up to set email alerts
|

Circular Dichroism Techniques for the Analysis of Intrinsically Disordered Proteins and Domains

Abstract: Circular dichroism (CD) spectroscopy is a simple and powerful technique, which allows for the assessment of the conformational properties of a protein or protein domain. Intrinsically disordered proteins (IDPs), as discussed throughout this series, differ from random coil polypeptides in that different regions present specific conformational preferences, exhibiting dynamic secondary structure content [1]. These dynamic secondary structure elements can be stabilized or perturbed by different chemical (solvent, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
92
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 27 publications
12
92
0
Order By: Relevance
“…While well-folded proteins classically denature with a cooperative transition, proteins containing a high proportion of unstructured polypeptide exhibit non-cooperative transitions. 40 A thermal denaturation scan for OS-9 ΔMRH showed a linear decrease in ellipticity at 222 nm with increasing temperature (Figure 7B), ultimately reaching a plateau at 85 °C, suggesting that the C-terminal domain of OS-9 is intrinsically disordered. A similar CD spectral analysis of the isolated OS-9 CTE, a major in vitro Grp94 binding site, showed minima at 208 and 222 nm suggesting a predominantly helically structured peptide (Figure 7C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While well-folded proteins classically denature with a cooperative transition, proteins containing a high proportion of unstructured polypeptide exhibit non-cooperative transitions. 40 A thermal denaturation scan for OS-9 ΔMRH showed a linear decrease in ellipticity at 222 nm with increasing temperature (Figure 7B), ultimately reaching a plateau at 85 °C, suggesting that the C-terminal domain of OS-9 is intrinsically disordered. A similar CD spectral analysis of the isolated OS-9 CTE, a major in vitro Grp94 binding site, showed minima at 208 and 222 nm suggesting a predominantly helically structured peptide (Figure 7C).…”
Section: Resultsmentioning
confidence: 99%
“…While the band at 222 nm derives from α-helical structure, the band at 204 nm indicates the presence of intrinsically disordered regions and arises from the combination of two minima, one at 200 nm arising from random coil and the other at 208 nm arising from α-helical content. 40; 41 …”
Section: Resultsmentioning
confidence: 99%
“…Comparison of their ability to block hydrogen exchange revealed that unlike urea, GdnHCl does not form H-bonds with the polypeptide but instead stacks against planar groups in the backbone and side chains such as Asn or aromatic residues [86]. Both urea and GdnHCl favor formation of the highly extended PPII conformation in IDPs and denatured globular proteins, monitored by the far-UV CD signal near 220 nm [44, 68, 87, 88]. PGR shows an increase in PPII content at high concentrations of urea (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A cell path length of 1 mm was used, with protein concentrations between 10–20 mg/ml (4–6 uM). Data was converted to mean residue molar ellipticity ([θ] in deg cm 2 dmol-1) [equation 1] and the percent helicity [equation 2] was estimated using [θ]222 [27, 49]. [θ]=(100θ)(clN) Where θ is the measured ellipticity (mdeg), c is the sample concentration (mM), 1 is the path length (cm), and N is the number of amino acids.…”
Section: Methodsmentioning
confidence: 99%
“…(i) Small-angle X-ray scattering (SAXS)/Wide-angle X-ray scattering (WAXS), which has been previously used to characterize highly flexible systems in solutions including disordered proteins [25] and have the additional advantage to provide information about molecular size, shape, aggregation, conformation changes [26]. (ii) Circular dichroism (CD), widely used to describe the secondary structure of proteins in solution [27]. (iii) Fourier transform infrared spectroscopy (FTIR) that provides information on the secondary structure of proteins not only in solution but also when they interact with solid surfaces or soluble molecular partners [28].…”
Section: Introductionmentioning
confidence: 99%